Assessment of Calprotectin Protein in H. Pylori Positive Persons - Salim Hussein Hassan1 , Balqees Sadoon Jasim 2, Maytham Salim AL-Nasrawii 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Helicobacter pylori (H. pylori) is amongst the most infectious and almost half of the country’s population is affected by a chronic bacterial infection. H. pylori evoke an inflammatory reaction of the host epithelium, leading to induction of immune cells which exhibit as gastritis. There is little knowledge of how pylori remain in the host’s antimicrobial agents, such as calprotectin (CP), which is found through an immune response. Objective: The purpose of this study was to evaluate the role of fecal calprotectin (FC) in subjects with gastric ulcer and correlation of it with H. pylori. Methods: 25 patients with gastric ulcer and 25 healthy controls were included in a prospective study. Samples of blood are taken IgG antibody H pylori and stool specimen for measured of calprotectin level. Results: All gastric ulcer patients infected with H pylori. From a total of 25 patients participating in this study 8 were man and 17 women with the mean age 40.6±15.8. There was a statistically meaningful difference between the groups analyzed (p=0.0001) dependent on the calprotectin level. Also found significant association between sex and calprotectin level according to the positivity of H pylori.Conclusion: There’s a significant statistical between fecal calprotectin level and H. pylori infection in gastric ulcer patients.